Karakteristik Karkas dan Non Karkas Ayam Broiler Jantan dan Betina pada Umur Pemotongan 30 Hari - Ulupi, N.; Nuraini, H.; Parulian, J.; Kusuma, S. Q. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
The population of commercial broiler chickens in Indonesia is increasing along with the high level of consumption of Indonesian poultry meat. The difference in the weight of broiler chicken harvest due to sex differences allows for differences in the percentage of carcass, non carcass and physical quality of broiler chicken meat. The aim of study was to analysis the sex differences in broiler chickens against the carcass and non carcass characteristics produced. 10 broiler chickens, each of male and female aged 30 days randomized from 14 000 broiler chickens that maintained in closed house were analyzed. The variables observed were carcass characteristics (carcass percentage, cut up of carcass, edible and non edible carcass components, and physical quality of breast meat) and non carcass characteristics (non carcass components). The data obtained were analyzed using the t-test. The average body weight of male and female chickens were 1 834.10 g and 1 659.40 g. The carcases percentage of male and female broilers were 69.38% and 70.78%. The bone percentage of male and female broilers were 17.27% and 15.56%. The cooking shrinkage value of male and female broilers breast meat were 36.32% and 42.50%. As a conclusion, male broilers with greater body weight produced a smaller significant of carcas percentage, and a significantly greater of bone percentage, but had better in physical quality than female broiler chickens.